2015
DOI: 10.1590/1807-57622014.1345
|View full text |Cite
|
Sign up to set email alerts
|

PET-Saúde: uma experiência potencialmente transformadora no ensino de graduação

Abstract: IntroduçãoO processo de formação de profissionais na modernidade toma, como referência, o processo de trabalho determinado e organizado sob os princípios do modo de produção capitalista: produtividade e competitividade. No campo da saúde, essa direcionalidade da formação tem suscitado discussões a respeito de sua adequação à organização do processo de trabalho na saúde tal como preconizado pelos moldes tayloristas, assim como discussões que compreendem a intrínseca articulação entre a formação e o processo de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
3
0
7
Order By: Relevance
“…A parceria ensino-serviço promove melhora na qualidade do serviço porque a presença dos estudantes estimula os profissionais a desenvolver uma prática reflexiva, o que reorienta o serviço e amplia e qualifica suas práticas [33][34][35][36][37] . No entanto, a valorização da presença dos estudantes nesses cenários pelos profissionais e gestores das próprias unidades não é consenso 38 .…”
Section: Discussionunclassified
“…A parceria ensino-serviço promove melhora na qualidade do serviço porque a presença dos estudantes estimula os profissionais a desenvolver uma prática reflexiva, o que reorienta o serviço e amplia e qualifica suas práticas [33][34][35][36][37] . No entanto, a valorização da presença dos estudantes nesses cenários pelos profissionais e gestores das próprias unidades não é consenso 38 .…”
Section: Discussionunclassified
“…Succinctly, valuing the formation of ethical and socially committed professionals. 23 The commitment to training is also constituted in the interactivity and in the dialogue between professors and students that are fundamental attitudes in the reflection, whether in the theoretical or practical field. The dialogue between professor and student is a basic precept in stimulating reflection in the theoretical context and in the space of practices.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that the teaching and learning process, based on professional practices carried out in the daily routine of health services, provides a multiprofessional and interdisciplinary experience. 15 The interaction between health professionals and students from different areas promotes reflection on professional roles and reduces prejudices and differences, thereby preparing students to work on interprofessional teams. 13 In relation to methodologies, the findings indicate a higher frequency of use of traditional methodologies by professors who do not accompany students in health services.…”
Section: /15mentioning
confidence: 99%